New challenges in High Education: Analysis of the results and difficulties experienced by students of School Teacher Degree (University of Salamanca) during the elaboration of the Undergraduate Dissertation - Vicario-Molina, Isabel; Martín-Pastor, Elena; Gómez-Gonçalves, Alejandro; González Rodero, Luis María (Revista Complutense de Educación, 2020)
In Spanish Universities, an Undergraduate Dissertation (UD) is the last step on the formative period of undergraduate students and develops a key role in the evaluation of competencies, knowledge and acquired abilities. This course is a challenge for undergraduate students because they have to confront several difficulties during the elaboration process. The origin of this research is the study of the factors that influence these difficulties, and also the study of the factors that determine the final result of the UD. Therefore, the aim of this paper is to analyze the results -grades and satisfaction- and the difficulties experienced by university students during the elaboration of their UD. In order to achieve this objective, we have analyzed the opinion of 251 graduated students from the University of Salamanca, who had already finished their degree as Primary or Infant School Teachers. Students completed an on line questionnaire that was designed specifically for this study with 17 items. The results indicate that main challenges experienced by students are related with the management of APA style and with the difficulties to work consistently on the project and other activities. Moreover, the level of satisfaction with the project is lower than the grade obtained. Lastly, the role of the supervisor seems to be an important predictor of project results. This study contributes to reinforce existing literature about UD, going in detail in several aspects. Concretely, in those related with the difficulties that can emerge during the elaboration process and with the variables related with the final results.
Keywords: undergraduate dissertation; difficulties; satisfaction; higher education